Exploring redox activity in a LiCoPO4–LiCo2P3O10 tailored positive electrode for 5 V lithium ion batteries: rigid band behavior of the electronic structure and stability of the delithiated phase. Issue 12 (7th March 2018) - Cherkashinin, Gennady; Lebedev, Mikhail V.; Sharath, Sankaramangalam U.; Hajduk, Andreas; Nappini, Silvia; Magnano, Elena
Abstract : The novel LiCoPO4 –LiCo2 P3 O10 cathode material: a rigid band behavior of the electronic structure. Abstract : The stability of the novel highly electronically conductive LiCoPO4 –LiCo2 P3 O10 tailored polyphosphate is studied under electrochemical delithiation using quasi in situ depth-resolved synchrotron photoelectron spectroscopy, X-ray absorption spectroscopy and X-ray diffraction. The cathode material exhibits a rigid band behavior of the electronic structure and is stable in its fully delithiated state without amorphization in air.